2020
DOI: 10.1111/jch.13750
|View full text |Cite
|
Sign up to set email alerts
|

The HOPE Asia Network activity for “zero” cardiovascular events in Asia: Overview 2020

Abstract: The impact of hypertension-related cardiovascular disease and target organ damage, and therefore the benefits of blood pressure (BP) control, is greater in Asian than in Western countries. Asia-specific features of hypertension and its effective management are important and active areas of research. The Hypertension Cardiovascular Outcome Prevention and Evidence in Asia (HOPE Asia) Network was formed in 2016and is now a member of the World Hypertension League. The main goal of the HOPE Asia Network is to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 102 publications
0
17
0
Order By: Relevance
“…18 The HOPE Asia Network was established in 2016 and is a member of the World Hypertension League. 19,20 The mission of the HOPE Asia Network is to improve the management of hypertension and organ protection toward achieving "zero" cardiovascular events in Asia. 19,20 This has become even more relevant in the current pandemic, with high rates of infection in several Asian countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The HOPE Asia Network was established in 2016 and is a member of the World Hypertension League. 19,20 The mission of the HOPE Asia Network is to improve the management of hypertension and organ protection toward achieving "zero" cardiovascular events in Asia. 19,20 This has become even more relevant in the current pandemic, with high rates of infection in several Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The mission of the HOPE Asia Network is to improve the management of hypertension and organ protection toward achieving "zero" cardiovascular events in Asia. 19,20 This has become even more relevant in the current pandemic, with high rates of infection in several Asian countries. This guidance from the HOPE Asia Network summarizes the latest findings on COVID-19 and hypertension, including evidence-based recommendations for the management of hypertension during the current pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…18) The increase in daytime BP/HR is associated with exercise and might be a reflection of an increase in physical activity during the daytime. 19) By using the sleep rate mode, the physiological diurnal HR change can be maintained, and the pacemaker battery life can be extended due to a reduced pacing rate. Lower rates of atrial pacing have been demonstrated to reduce the rate of atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…15 Asian evidence and guidelines have been discussed by Network members to reach consensus on key topics such as target BP level, practical application of HBPM and ABPM, salt intake and preferred antihypertensive medications, among others, resulting in the publication of a number of consensus documents and Asiaspecific recommendations that cover nearly all major topics relating to the management of hypertension. [15][16][17][18][19][20] These documents should contribute to optimizing individual and population-based hypertension management strategies in Asian countries/regions. 20 The HOPE Asia Network model is an excellent example of how interpretation, modification, and dissemination of international best practices at a regional level, in collaboration with local hypertension societies, can be used to benefit specific populations.…”
Section: The Hope Asia Networkmentioning
confidence: 99%
“…It is endorsed by the World Hypertension League, and is an affiliated organization of the International Society of Hypertension. 15 Hypertension management, and mitigation of the negative cardiovascular effects of hypertension, is being addressed by local hypertension societies in Asia. There are several strategies likely to be effective in managing hypertension in Asia based on the local characteristics of the disease.…”
Section: The Hope Asia Networkmentioning
confidence: 99%